Features of Social Networking in Reaching Professional Goals of University Educators - Bordovskaia N.V; Tulupyeva T.V; Tulupyev A.L; Azarov A.A (Moscow State University of Psychology and Education, 2017)
The paper focuses on features of Internet support of professional activities in modern university educators and of learning activities in students through the organization of a new web-based space for communication between instructors and learners. It describes the authors' experience in creating such space basing on social networking within the context of modern educational environment of university. Four major groups of university educators' professional goals which can affectively be attained using social-networking educational resources are identified. Based on an observational study, we offer techniques that can be used for personality traits identification in students, for providing more individualized instruction and making information concerning education and achievements in an academic course more accessible, as well as for control and optimization of interactions initiated either by educator or by students (including interactions among students and those between students and educators). The effectiveness of the new instructor/learner communication channel among the participants of the educational process is proved empirically. This work was supported by grants: Russian Foundation for Basic Research 14-07-00694-а and Russian Foundation for Humanities 16-06-00486